EUPHEMISMS AS AN OBJECT OF STUDY IN LINGUISTICS - Уahуoуеva, Mohinabonu (Innovative Development in Educational Activities, 2023)
Euphemisms are classified into pure and contextual euphemisms. The function of pure euphemisms is directly derived from their own meanings. This article is devoted to the euphemisms as an object of study in linguistics.